Educational diagnostics "in" and "with regard to" school reality - Maria Groenwald (University of Lower Silesia, 2011)
In the paper I present changes occurring within the realm of educational diagnostics which are initiated (1) by educational diagnostics itself (as a developing sub-discipline of pedagogy); (2) by education, the new diagnostic needs of which can be fulfilled (a) as diagnoses "in" schools conducted by teachers for their own purposes, students and establishments; (b) as diagnoses "with regard" to schools conducted by external institutions. Currently there appears a dominance of the diagnosis "with regard to" school, which, given its common approval, needs to the teacher-run "internal" diagnosis being appropriated or deformed. As a result, the diagnoses of the state of education prove incomplete, sometimes abstract, and while being only seeming, they favour the running of seeming education and upbringing at school.